Answer:
A (48)
Explanation:
let the father's age = x and his son's age = y
according to the question,
the sum of their ages is 74
×+y=74......equation 1
four years ago (i.e x-4 & y-4) father's age was twice as old as his son
x-4=2(y-4)
or, x-4=2y-8
x-2y=-4.......equation 2
now, in equation 1
x+y=74
hence,
x=74-y
substituting the values in equation 2
x-2y=-4
(74-y)-2y=-4
74-y-2y=-4
74-3y=-4
74+4=3y
3y=78
y=78/3
y=26
Hence the kid is 26 years old
x+y=74
x+26=74
x=74-26
x=48
Hence the dad is 48 years old